2022
DOI: 10.1103/physics.15.78
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Women in Physics is More Than a Numbers Game

Abstract: In intro-to-physics classes containing more women than men, women still feel out of place, implying that more needs to be done to make physics classrooms feel inclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Unfortunately the results of these studies that omit the Interest variable have been reported in the scientific press (12) with policy recommendations based on a purely causal interpretation.…”
mentioning
confidence: 98%
“…Unfortunately the results of these studies that omit the Interest variable have been reported in the scientific press (12) with policy recommendations based on a purely causal interpretation.…”
mentioning
confidence: 98%